Sistem Pendukung Keputusan Pemilihan Sales Terbaik Dengan Menggunakan Metode WASPAS - Felix Sihaloho, Juan (Bulletin of Data Science, 2024)
PT.Jovi Karunia Jaya is a company that sells medical equipment, parts such as thermometers, stethoscopes, oxygen cylinders, blood pressure monitors and others. In the company PT. Jovi Karunia Jaya has been accredited for excellent health and sales to the public. The problem that occurs in sales selection is that companies experience difficulty in selecting the best salesman to be promoted to sales manager because currently companies determine their best salesman by only looking at the amount of sales turnover generated by each salesman, but paying little attention to other factors. which can support the assessment, resulting in the management making the wrong choice and making a decision, and can also give the impression of favoritism towards one of the salesmen and can give rise to social jealousy. To overcome problems that occur at PT. Jovi Karunia Jaya to determine the best health sales, by making decisions using the WASPAS method so that the results are more efficient. The alert method is a method that can reduce errors or optimize estimates for selecting the highest and lowest values. Therefore, the role of decision support systems is needed in overcoming the problems currently faced. Based on calculations carried out using the WASPAS method, the highest ranking result was obtained, namely Nurhayati Saragih (A3) with a score of 5.3675.